2014
DOI: 10.1039/c3an01884a
|View full text |Cite
|
Sign up to set email alerts
|

reMelting curve analysis as a tool for enrichment monitoring in the SELEX process

Abstract: Current aptamer selection procedures enable limited control and transparency on how the DNA selection pool is evolving. Affinity tests and binding analyses are not always informative. Here we show that real-time PCR provides a valuable tool for the follow-up of aptamer selection. Limited time, work and amount of amplified ssDNA make this an interesting instrument to set-up a SELEX design and monitor the enrichment of oligonucleotides. reMelting Curve Analysis (rMCA) after reannealing under stringent conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 20 publications
2
33
0
1
Order By: Relevance
“…33 Although important, the above-mentioned methods extrapolate the selection for target-specific oligonucleotides from indirect events like library complexity or increased elution, which could be severely impacted by unforeseen biases common in SELEX protocols. The presented direct evaluation of the SELEX progression via SPR-based measurement of the target- affinity of the cycle-libraries overcomes this problem.…”
Section: ■ Discussionmentioning
confidence: 99%
“…33 Although important, the above-mentioned methods extrapolate the selection for target-specific oligonucleotides from indirect events like library complexity or increased elution, which could be severely impacted by unforeseen biases common in SELEX protocols. The presented direct evaluation of the SELEX progression via SPR-based measurement of the target- affinity of the cycle-libraries overcomes this problem.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The 80‐mer library was combinatorially synthesized by mixing the DNA nucleotides A:C:G:T at a molar ratio of 3:3:2:2.4 to achieve equal probability incorporation of each nucleotide in the core region (Pollard et al, ). The 20‐mer flanking sequences and associated primers (Table S‐I; Supporting Information) are ones commonly employed in conventional SELEX (Janssen et al, ; Ouellet et al, ; Vanbrabant et al, ), and were utilized here due to their suitability for SYBR green qPCR amplification (Janssen et al, ). For this work, both flanking sequences had their reverse complement synthesized, with the complement to the 5′ and 3′ flanking sequences denoted in Table S‐I (Supporting Information) as 5′‐Comp and 3′‐Comp, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…, by FACS, 68 EMSA, 47 filter binding, 127 or capillary electrophoresis (CE)), 128 or (iii) convergence of the aptamer species ( e.g. , by Restriction Fragment Length Polymorphism (RFLP), 129 melting curve, 130 Cot analysis, 131 or HPLC). 132 A recent study compared RFLP, melting curve, fluorescence, QPCR, and bulk binding affinity measurement assays to monitor the progress of SELEX against streptavidin concluded that these assays were all equally informative.…”
Section: Emerging Concepts In Selex and Aptamer Fieldsmentioning
confidence: 99%